ความหนาแน่นฟลักซ์จากแม่เหล็กถาวรในต้นแบบตู้เย็นแม่เหล็กที่มีโรเตอร์แม่เหล็กอ่อน - เนียมจันทร์ นวลจุฑา; ใหญ่ประเสริฐ ชัยโรจน์; ศิริสถิตย์กุล ชิตณรงค์ (Thai Journal of Science and Technology, 2019)
Abstract Magnetic refrigerator is a new technology that can reduce the temperature beneath the room temperature by virtue of heat transfer from magnetocaloric materials in changing magnetic fields. In this research, the cooling system is composed of 4 neodymium-iron-boron permanent magnets and soft magnetic carbon low-carbon steels acting as pole faces, linkages between 2 bars of permanent magnets surrounding a soft magnetic rotor. The COMSOL Multiphysics program was used to simulate the distribution in magnetic flux density and analyze the optimum parameters in designing a magnetic refrigerator. The magnetic flux densities as high as 1.13 T and as low as 0.07 T were obtained by using (1) the width of the air gap to be occupied by magnetocaloric materials around 10 mm, (2) the width of the pole faces of about 15 mm, and (3) the approximate width of permanent magnets of 30 mm. Keywords: magnetic refrigerator; magnetocaloric effect; neodymium-iron-boron; low carbon steel; magnetic flux density